2014
DOI: 10.1186/1752-1947-8-207
|View full text |Cite
|
Sign up to set email alerts
|

An aggressive vertebral hemangioma in pregnancy: a case report

Abstract: IntroductionPregnancy-related compressive myelopathy secondary to vertebral hemangioma is a rare occurrence and its treatment antepartum is rare.Case presentationA 19-year-old North African woman in her 38th week of pregnancy presented with paraplegia that progressed within 2 days after a rapidly progressive weakness of her lower limbs. Magnetic resonance imaging studies showed compression of her spinal cord in front of the fourth thoracic vertebra for suspected tuberculous spondylitis. A Caesarean section was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…12,48,51,59,61,64,67 Aggressive vertebral hemangiomas are also more common in adults but have been reported in children as well. 11,18,44,54 It is generally agreed that surgical intervention is warranted when hemangiomas cause pain or neurological symptoms, however the optimal treatment strategy is controversial.…”
mentioning
confidence: 99%
“…12,48,51,59,61,64,67 Aggressive vertebral hemangiomas are also more common in adults but have been reported in children as well. 11,18,44,54 It is generally agreed that surgical intervention is warranted when hemangiomas cause pain or neurological symptoms, however the optimal treatment strategy is controversial.…”
mentioning
confidence: 99%
“…For spine tumors in pregnancy, a recent report found that giant cell tumors, hemangiomas, and schwannomas were the most frequent tumor types [10]. There have been case reports describing these tumors along with spinal meningiomas and ependymomas [8,[11][12][13][14][15]. Spinal ependymomas are rare benign, slow-growing tumors that can present with back pain and neurologic changes depending on their location within the cord [2,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Hemangioma is usually asymptomatic and incidentally discovered (4). About 1% of cases may be symptomatic (aggressive hemangiomas) (1,8), which present with merely pain or alongside neurological involvement. They are commonly found in the thoracic region and become symptomatic followed by mild trauma or at the end of pregnancy (third trimester of pregnancy) or even spontaneously (2,6).…”
Section: Discussionmentioning
confidence: 99%
“…Its appearance is characterized by honey comb, corduroy in the lateral radiography or CT sagittal and coronal (1,6,8). Asymptomatic hemangiomas usually involve the vertebral body partly with posterior elements not involved.…”
Section: Discussionmentioning
confidence: 99%